2019
DOI: 10.1038/s41598-019-47546-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Strain Effects on Photoelectrochemical Performance of Flexible ZnO Electrodes

Abstract: In this report, the growth of zinc oxide (ZnO) nanocrystals with various morphologies, nanoflower, nanosheet, and nanorod, on flexible stainless steel (SS) foils to be utilized as photoanodes in photoelectrochemical (PEC) solar cells has been presented. It has been aimed to provide flexibility and adaptability for the next generation systems with the incorporation of SS foils as electrode into PEC cells. Therefore, physical deformation tests have been applied to the prepared ZnO thin film photoanodes. These th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…As demonstrated in Figure 7b, the best value of ABPE efficiency attained 2.05% at 490 nm and 1 V. Both IPCE and ABPE have a maximum value at 490 nm. This wavelength is very near to the SPR absorption area for Au NPs [91]. As result, the observed improved PEC performance could be attributed to the plasmonic-enhanced light absorption with a huge increase in the charge generation.…”
Section: Photo-electrochemical (Pec) Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…As demonstrated in Figure 7b, the best value of ABPE efficiency attained 2.05% at 490 nm and 1 V. Both IPCE and ABPE have a maximum value at 490 nm. This wavelength is very near to the SPR absorption area for Au NPs [91]. As result, the observed improved PEC performance could be attributed to the plasmonic-enhanced light absorption with a huge increase in the charge generation.…”
Section: Photo-electrochemical (Pec) Studiesmentioning
confidence: 84%
“…Additionally, plasmon energy transfer (PET) from plasmon resonant Au surfaces to adjoining ZnO decreases the distance of the travel holes to the electrolyte and, consequently, enhances the J ph value. Additionally, the light-concentrating effect due to the localized strong electric field around the Au NPs can improve the photogeneration rate of electron-hole pairs near the Au/ZnO interface area due to the strengthened electric field intensity [90,91]. Further, the good conductivity of Au NPs over ZnO NRs leads to decreased charge-transfer resistance, suppresses charges recombination, and accelerates the transfer of an electron from the ZnO NRs surface to the electrolyte [53].…”
Section: Photo-electrochemical (Pec) Studiesmentioning
confidence: 99%
“…Khalafi et al [113] synthesized pure ZnO NPs using a Chlorella aqueous extract and reported a hexagonal wurtzite structure (19.44 nm; calculated from Debye–Scherrer equation) as determined by the XRD pattern. Abdullayeva et al [115] investigated the crystallinity of nanoflower-, nanosheet-, and nanorod-like three-dimensional ZnO nanostructures. According to the XRD patterns, all ZnO nanostructures were the hexagonal wurtzite type from the (100), (002), and (101) of Miller–Bravais indices.…”
Section: Physicochemical Characterization and Toolsmentioning
confidence: 99%
“…More precisely, the measured optical constants associated with Ag and DLC films, which are obtained under the same deposition conditions were introduced in our FDTD modeling in order to be very close to the realistic behavior of the investigated multilayer electrodes. Moreover, FDTD modeling method is considered effective, been able to provide an accurate solution of Maxwell equation even for more complicated structures as it is illustrated by various published works Stelling et al, 2017;Abdullayeva et al, 2019). Therefore, the use of accurate FDTD-based numerical modeling supported by ellipsometry technique has enabled exciting opportunities to efficiently predict the performance of the investigated DLC/Metal/DLC structure and has contributed to reach the highest Haacke FoM parameter for high-performance thin-film solar cell and optoelectronic applications.…”
Section: Performance Assessment Of Dlc/metal/dlc Transparent Electrodesmentioning
confidence: 99%